The area of Győr in the light of economic and social aspects –spatial relationship analysis - Szabolcs (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2018)
The roles of cities are steadily growing in value. Additionally, over the past decade some changes can be detected in urban governance. In the early 1990s in Western Europe the macroregional governance – as a new way of governance – already came into focus and the cooperation among the city and its suburban settlements, regional coordination, spatial planning at a regional level and macro-regional institutional organisations support the city regions. Thus, as the subject of this study, city regions or metropolitan areas are presented, the definition of which includes their agglomeration and the adjacent settlements. What methods are suitable to research the division of functions among settlements? What benefits are to be gained from facilitating their harmonisation? What role does a central settlement play in its agglomeration and what is its responsibility in the full provision of the missing functions in the case of small settlements and villages with deficiencies? In this study some additional scientific information will be provided to enable these questions to be answered. Taking Győr and its agglomeration as the object of the study and processing data collected from an empirical research allocated by the VIDGY (Vehicle Industrial District in Győr) research, the method of spatial relationship analysis is used.